2021
DOI: 10.1186/s12888-021-03230-1
|View full text |Cite
|
Sign up to set email alerts
|

Decision making under ambiguity and risk in adolescent-onset schizophrenia

Abstract: Objective Numerous studies have identified impaired decision making (DM) under both ambiguity and risk in adult patients with schizophrenia. However, the assessment of DM in patients with adolescent-onset schizophrenia (AOS) has been challenging as a result of the instability and heterogeneity of manifestations. The Iowa Gambling Task (IGT) and Game of Dice Task (GDT), which are frequently used to evaluate DM respectively under ambiguity and risk, are sensitive to adolescents and neuropsychiatr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 59 publications
1
2
0
Order By: Relevance
“…While both groups selected more cards when loss probability was lower, the degree of this adjustment was significantly larger in non-SSD participants. Our findings were largely consistent with past studies regarding altered risk adjustment in schizophrenia (Heerey et al, 2008;Hutton et al, 2002;Li et al, 2021;Martin et al, 2015;Pedersen et al, 2017). Notedly, when comparing risk-taking separately during 1-loss-card and 3-loss-card conditions, we observed no group differences in either risk-taking or deviation from optimal decision.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…While both groups selected more cards when loss probability was lower, the degree of this adjustment was significantly larger in non-SSD participants. Our findings were largely consistent with past studies regarding altered risk adjustment in schizophrenia (Heerey et al, 2008;Hutton et al, 2002;Li et al, 2021;Martin et al, 2015;Pedersen et al, 2017). Notedly, when comparing risk-taking separately during 1-loss-card and 3-loss-card conditions, we observed no group differences in either risk-taking or deviation from optimal decision.…”
Section: Discussionsupporting
confidence: 92%
“…For instance, in one study, individuals with both chronic and first-episode psychosis adjusted their bets to a lesser extent in response to changing probability compared to controls (Hutton et al, 2002). Another study found that individuals with adolescent-onset schizophrenia made fewer optimal choices and adjusted their behavior less according to negative outcomes on the previous decision (Li et al, 2021). Despite this work, much remains unknown about risky decision-making in schizophrenia.…”
Section: Introductionmentioning
confidence: 99%
“…MoCA < 26 indicates mild cognitive impairment. The Chinese version used in this study has been widely used in a sample of Chinese adolescents [41].…”
Section: Measurementioning
confidence: 99%